Non-conventional learning on sustainable development : achieving the SDGs - Walter Leal Filho (Environmental sciences Europe, 2021)
Learning has been identified as a critical tool for the achievement of sustainable development. But whereas the literature predominantly focuses on the use of classroom-based teaching methods and approaches, there is a perceived need to shed some light on the potential role which can be played by non-conventional learning. Based on the relevance of addressing this need, this commentary describes the role of non-conventional learning methods in supporting the achievement of the UN Sustainable Development Goals. In particular, it discusses the contribution of non-conventional teaching as a catalyst for a more active participation of learners, and also shows some of the trade-offs.
Keywords: Learning; Methods; SDGs; Sustainability